Body, language and mind (Cognitive linguistics research, 2007)
The first volume of Body, Language and Mind focuses on the concept of embodiment, understood in most general terms as "the bodily basis of phenomena such as meaning, mind, cognition and language". The volume offers a representative, multi- and interdisciplinary state-of-the-art collection of papers on embodiment and brings together a large variety of different perspectives, from cognitive linguistics, cognitive science, philosophy, psychology, semiotics and artificial intelligence.